STUDENTS PERCEPTION ABOUT GOOGLE TRANSLATE AS MEDIA FOR TRANSLATING ENGLISH DESCRIPTIVE - Desta Gloria Siahaan; Iis Aprianti; Puji Hariati; Winter Purba (JETAL: Journal of English Teaching & Applied Linguistic, 2022)
The aim of this study to know students’ perception of Google Translate as Media for Translating English Descriptive Text at Fifth Semester of English Department Nommensen HKBP University. Questionnaires which formulated in google form are formulated as instrument to collect students’ responds on the usage of google translate in translating source to target. The questionnaire sheet consists of twelve questions about students’ perception of Google Translate as media for translating English descriptive text. The source of data in this study was taken by the fifth-semester student of English Department. There are twenty students have been filled the questionnaire sheet. This study was applied a descriptive qualitative design. The findings from the data analysis, Students have different positive and negative perception about Google Translate as media for translating English descriptive text. Students really like using Google translate as media for translating English descriptive text because make students easier. Students can translate text faster than open a dictionary. Google translate help students improve vocabulary with good intonation. They feel happy because it is easier to use but Google translate incorrect to translate in level of sentence. Based on their perceptions state that Google translate can be used as an alternative ways in teaching and learning activities.